2014
DOI: 10.1177/0022022114563749
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Control Strategies Regulated by Urgency and Interpersonal Harmony

Abstract: People use control strategies to improve their physical as well as interpersonal situations. Previous research has maintained that Japanese, compared with North Americans, are more oriented toward secondary control (changing oneself) than primary control (changing one’s circumstances). However, Heckhausen and Schulz’s work suggests dominance of primary control over secondary control across cultures. The conflicting views regarding Japanese control orientations are reconciled by considering situational variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 24 publications
0
12
1
1
Order By: Relevance
“…Harmony refers to the extent to which an individual values peaceful and concordant interpersonal relationships. Individuals with high harmony give priority to social relationships, strive to maintain them (Oyserman et al, ; Sawaumi, Yamaguchi, Park, & Robinson, ), and have high tolerance for interpersonal transgressions (Leung, ). As a major value in China (Chen, ), harmony serves as a guiding principle for interpersonal behaviours (Hwang, ), but it has received limited attention in research that examines coworker relationships (Leung, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harmony refers to the extent to which an individual values peaceful and concordant interpersonal relationships. Individuals with high harmony give priority to social relationships, strive to maintain them (Oyserman et al, ; Sawaumi, Yamaguchi, Park, & Robinson, ), and have high tolerance for interpersonal transgressions (Leung, ). As a major value in China (Chen, ), harmony serves as a guiding principle for interpersonal behaviours (Hwang, ), but it has received limited attention in research that examines coworker relationships (Leung, ).…”
Section: Introductionmentioning
confidence: 99%
“…Harmony as a unidimensional construct has been validated in both eastern and western studies (e.g. Sawaumi et al, ; Schwartz, ), such as with samples from 49 nations (Schwartz, ). Originating from China, the cultural value of harmony endorses a favourable relationship amongst people, things, and/or ideas (Li, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some recent research has found that Asians may prefer to use a primary coping control as opposed to secondary coping (Sawaumi, Yamaguchi, Park, & Robinson, 2015). A recent study by English et al (2015), found that secondary coping was adaptive for both Westerners and (non-Chinese) Asians living in China.…”
Section: Discussionmentioning
confidence: 99%
“…Among American college students in California, Lam and Zane ( 2004 ) found that Asian Americans used secondary coping more often than European Americans, while Euro-Americans used more primary coping. Secondary coping seems to be more strongly associated with Asian ethnic groups as opposed to Western (or non-Asian) groups, however one recent study found that Asians (Japanese students) may in fact prefer primary controls (see recent study by Sawaumi et al 2015 ).…”
Section: Cultural Differences In Copingmentioning
confidence: 96%